Innovations and Advances in Computer Sciences and Engineering - Sobh, Tarek; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Innovations and Advances in Computer Sciences and Engineering includes a set of rigorously reviewed world-class manuscripts addressing and detailing state-of-the-art research projects in the areas of Computer Science, Software Engineering, Computer Engineering, and Systems Engineering and Sciences. Innovations and Advances in Computer Sciences and Engineering includes selected papers form the conference proceedings of the International Conference on Systems, Computing Sciences and Software Engineering (SCSS 2008) which was part of the International Joint Conferences on Computer, Information and Systems Sciences and Engineering (CISSE 2008). Topics Covered: Signal and Image Processing: Content Based Video Retrieval, Character Recognition, Incremental Learning for Speech Recognition, Signal Processing Theory and Methods, and Vision-based Monitoring Systems. Software and Systems: Activity-Based Software Estimation, Algorithms, Genetic Algorithms, Information Systems Security, Programming Languages, Software Protection Techniques, Software Protection Techniques, and User Interfaces. Distributed Processing: Asynchronous Message Passing System, Heterogeneous Software Environments, Mobile Ad Hoc Networks, Resource Allocation, and Sensor Networks. Advanced and innovative techniques in computing: e-Science and Virtual Instrumentation, Fault-Tolerant Scheduling, Grid Computing, Microcracking in Cortical Bones, Service-oriented Architectures, and Virtualization in Data Warehouses.
Keywords: Engineering; Computer hardware; Software engineering; Electronics; Engineering; Electronics and Microelectronics, Instrumentation; Computer Hardware; Software Engineering/Programming and Operating Systems